Urine collection practices in a small rural hospital: Evaluation of alignment with antimicrobial stewardship guidelines. - Irwin, Jennifer; Forrester, Leslie (Canadian Journal of Infection Control / Revue Canadienne de Prévention des Infections)
Background: The diagnosis of a symptomatic urinary tract infection (UTI) can be challenging among elderly patients, resulting in an increased risk for specimen collection and treatment of asymptomatic patients. The Vancouver Coastal Health Authority's Antimicrobial Stewardship Guidelines provide a systematic approach to support clinicians in the assessment and treatment of UTIs. The purpose of this quality review was to evaluate if urine collection practices were in alignment with the guidelines. Methods: The review involved a retrospective examination of all urine specimens collected from medical and surgical patients of a small rural hospital from September 1, 2015 to August 31, 2016. A survey of staff was also conducted to evaluate the interdisciplinary team's knowledge of urine collection and interpretation and to assess concordance with the guidelines. Results: 318 urine cultures were reviewed, of which only 78 (24.5%) met microbiologic criteria and were considered to be positive cultures. A large proportion of samples resulted in mixed organisms. There was a highly statistically significant relationship between urinalysis and a positive culture (Fisher's exact test p < 0.0001). A positive urine culture (> 100 million CFU/L) was statistically significantly more likely to be observed when there was a positive urinalysis. Conclusions: Older adults represent a large and growing population of hospitalized patients. Diagnosis of a symptomatic UTI in the elderly can pose challenges. Urine cultures are frequently obtained and a high proportion sent for culturing with missing or negative urinalysis. Urinalysis results are pertinent in the diagnosis of a UTI as there is correlation between a positive urinalysis and a positive urine culture. Adoption of a systematic approach in the management of UTIs would result in consistent and appropriate assessment and treatment of UTIs for elderly patients.